1999
DOI: 10.1063/1.479371
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for calculating the properties of intramolecular hydrogen bonds. Excited state proton transfer

Abstract: A series of molecules related to malonaldehyde, containing an intramolecular H-bond, are used as the testbed for a variety of levels of ab initio calculation. Of particular interest are the excitation energies of the first set of valence excited states, n* and *, both singlet and triplet, as well as the energetics of proton transfer in each state. Taking coupled cluster results as a point of reference, configuration interaction-singles-second-order Møller-Plesset ͑CIS-MP2͒ excitation energies are too large, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…481 S ring (66). 528 514 δ CO (36), S ring (15), R ON (7) 534 Ph ring (25), δ CO (17), R ON (6) 566 Ph ring (30) 630 ring def a Wave packet motion from ref . b Frequencies CIS/6-31G* scaled by 0.9. c Notation for the internal coordinates and PED description.…”
Section: Resultsmentioning
confidence: 99%
“…481 S ring (66). 528 514 δ CO (36), S ring (15), R ON (7) 534 Ph ring (25), δ CO (17), R ON (6) 566 Ph ring (30) 630 ring def a Wave packet motion from ref . b Frequencies CIS/6-31G* scaled by 0.9. c Notation for the internal coordinates and PED description.…”
Section: Resultsmentioning
confidence: 99%
“…However, the large size of the systems is still precluded an advanced theoretical characterization (CASSCF, CCSD and CASPT2) of the potential energy surfaces of ESIPT. Fortunately, the recent calculations [14,27] showed that TDDFT can reliably predict the potential energy surface of ESIPT. In this work, we constructed the potential energy surface (PES) of ESIPT by TD [28] (B3LYP)/6-31G(d,p) theoretical calculations for the B3LYP/6-31G(d,p) ground state optimized structures.…”
Section: Computational Sectionmentioning
confidence: 99%
“…Even apart from the question of whether it is just the barrier heights that are needed to estimate the tunneling frequencies -this idea probably derives from Arrhenius and the transition-state theory, but in tunneling other parameters are also relevant -no consensus can be found between various methods to calculate these. Kar et al [83] reported a comparison of a number of calculations where the barrier heights in the ground state vary from −1.8 kcal mol −1 (not a barrier at all) to +20.2 kcal mol −1 . In the excited states, this is even worse.…”
Section: Short Historical Overview Of Tautomerization Dynamicsmentioning
confidence: 99%